KERUSAKAN BIJI KAKAO OLEH HAMA PENGGEREK BUAH (Conopomorpha cramerella Snellen) PADA PERTANAMAN KAKAO DI DESA MUNTOI DAN SOLIMANDUNGAN - Saida F. Azim; Daisy S. Kandowangko; Noni N. Wanta (COCOS, 2016)
ABSTRACTThe research aimed to damage cacao seed of is cacao moth (C. cramerella Snellen) was carried plants cocoa in the village Muntoi and village Solimandungan.The research was carried two village : (1) Muntoi (2) Solimandungan. To find out damage cacao seed of cacao moth attack to do is cacao fruit fission with figuring quantity damaged seed, and quantity healthy seed. quantity cacao fruit gaze have a lot of 25 fruit from to each sample location and by dividing 4 repetetion with interval harvesting 1 month that starts from November 2015 to February 2016. The research in use purposive sampling (sampling was by randomly) with take fruit is ripeness with characterized shape of the fruit is yellow. Precentage of damaged seed cacao of is cacao moth in the village Muntoi 18,25 % and village Solimandungan 50,20%. Damaged seed was to fruit cacao to plants cacao in the village Muntoi and village Solimandungan because have a controller by pruning and garden sanitation.Keywords : C. cramerella, Cacao moth, Cacao.